2011
DOI: 10.1002/hep.24208
|View full text |Cite
|
Sign up to set email alerts
|

Notch1 differentially regulates oncogenesis by wildtype p53 overexpression and p53 mutation in grade III hepatocellular carcinoma

Abstract: The tumor suppressor p53 is a key prognostic factor in hepatocellular carcinoma (HCC), yet only 35% of grade III tumors exhibit mutation of p53. Several other pathways have been implicated in HCC and, among these, the role of the Notch1/Snail pathway remains unclear. Therefore, we investigated the expression of p53, Notch1, and Snail proteins in HCC with regard to both clinical grade and p53 mutational status. Immunoblotting for p53 revealed that, whereas in many tumors increased p53 was a result of p53 mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 29 publications
3
29
0
Order By: Relevance
“…The inhibition of invasion by NICD and Snail coexpression was observed in both Hep3B cells (p53-null) and Huh7 cells (p53-mutant). On the other hand, in p53 WT cells such as HepG2, NICD and Snail coexpression promotes invasiveness [25]. In the present study, we showed NICD regulated invasion via Snail degradation in p53-null or p53-mutant status.…”
Section: Discussionsupporting
confidence: 49%
“…The inhibition of invasion by NICD and Snail coexpression was observed in both Hep3B cells (p53-null) and Huh7 cells (p53-mutant). On the other hand, in p53 WT cells such as HepG2, NICD and Snail coexpression promotes invasiveness [25]. In the present study, we showed NICD regulated invasion via Snail degradation in p53-null or p53-mutant status.…”
Section: Discussionsupporting
confidence: 49%
“…Activated Notch1 has been reported to directly bind p53 and inhibit its phosphorylation and transactivation (45), and a direct interaction between NICD4, p53, and murine double minute 2 (Mdm2) was recently shown to be important for Mdm2-mediated degradation of Notch (46). Conversely, modulation of p53 levels directly altered Notch levels in hepatocellular carcinoma, and p53 was required for Notch-induced growth and invasiveness (47). Notch may also be part of p53's antiapoptotic activity (48).…”
Section: Discussionmentioning
confidence: 99%
“…The protein of p53 and Fbxw7 were significantly decreased, Hes-1and NF-jB p65 were significantly increased in RITA siRNA cells compared to control siRNA cells (P < 0.05). and despite strong data indicating that Notch activation facilitates tumor progression in the liver [14][15][16][17], some reports have suggested otherwise [12,18,19]. Aberrant Notch1 and Notch3 gene expression has been observed in HCC and has been associated with modulation of cell growth and response to chemotherapy.…”
Section: Discussionmentioning
confidence: 90%